A Sex-Specific Analysis of the Predictive Value of Troponin I and T in Patients With and Without Diabetes Mellitus After Successful Coronary Intervention - Leutner, Michael; Tscharre, Maximilian; Farhan, Serdar; Taghizadeh Waghefi, Hossein; Harreiter, Jürgen; Vogel, Birgit; Tentzeris, Ioannis; Szekeres, Thomas; Fritzer-Szekeres, Monika; Huber, Kurt; Kautzky-Willer, Alexandra (Frontiers in Endocrinology, 2019)
Background: Elevated levels of troponin are associated with future MACE. Data on the prognostic value of high sensitive troponin T (hs-TnT) as compared to high sensitive troponin I (hs-TnI) in diabetic and non-diabetic patients are sparse. Methods: We analysed patients of a single-centre registry undergoing coronary stenting between 2003 and 2006. As a primary endpoint we assessed major adverse cardiac events (MACE), a composite of cardiovascular death, nonfatal myocardial infarction and nonfatal stroke according to sex and diabetes status using log-rank. As a second endpoint, we assessed the prognostic impact of hs-TnT and hs-TnI on MACE, adjusting for known confounders using Cox regression analysis. Results: Out of 818 investigated patients, 268 (32.7%) were female. Diabetes mellitus type 2 (T2DM) was diagnosed in 206 (25.2%) patients. After a mean follow-up of 6.6 ± 3.7 years, MACE occurred in 235 (28.7%) patients. The primary endpoint components of cardiovascular death occurred in 115 (14.1%) patients, MI in 75 (9.2%), and ischemic stroke in 45 (5.5%). Outcomes differed significantly according to sex and diabetes status (p=0.003). In descending order, MACE rates were as follows: female diabetic patients (40.8%), female non-diabetic patients (32.7%), male diabetic patients (28.9%), and male non-diabetic patients (24.8%). Additionally, females with diabetes were at higher risk of cardiovascular death compared to diabetic men (28% vs. 15%). Hs-TnI (HR 1.477 [95% CI 1.100-1.985]; p=0.010) and hs-TnT (HR 1.615 [95%CI 1.111-2.348]; p=0.012) above the 99th percentile were significantly associated with MACE. Both assays showed tendency towards association with MACE in all subgroups. Conclusion: Diabetic patients, particularly females, with known coronary artery disease had a higher risk of subsequent MACE. Both, hs-TnI and hs-TnT significantly correlated with MACE.